Suspected blood indicator in capsule endoscopy: a valuable tool for gastrointestinal bleeding diagnosis - Boal Carvalho, Pedro (2017)
Small bowel bleeding is a leading indication for small bowel capsule endoscopy. The Suspected Blood Indicator (SBI) is a software feature directed to automatically detect bleeding lesions during small bowel capsule endoscopy. Objective – We aimed to assess SBI diagnostic accuracy for small bowel haemorrhage or potentially bleeding lesions during small bowel capsule endoscopy for small bowel bleeding. Methods – Single-centre retrospective study including 281 consecutive small bowel capsule endoscopy performed for small bowel bleeding during 6 years. The investigators marked lesions with high bleeding potential (P2), such as angioectasias, ulcers and tumours, as well as active bleeding during regular small bowel capsule endoscopy viewing with PillCam SB2®. All small bowel capsule endoscopy were independently reviewed by another central reader using SBI. Results – Among the 281 patients, 29 (10.3%) presented with active haemorrhage while 81 (28.9%) presented with a P2 lesion. The most frequently observed P2 lesions were angioectasias (52), ulcers (15), polyps (7) and ulcerated neoplasias (7). SBI showed a 96.6% (28/29) sensitivity for active small bowel bleeding, with a 97.7% negative predictive value. Regarding P2 lesions, the SBI displayed an overall sensitivity of 39.5%, being highest for ulcerated neoplasias (100%), but significantly lower for angioectasias (38.5%) or ulcers (20.0%). Conclusion – Although SBI sensitivity for the automatic detection of potentially bleeding lesions was low, it effectively detected active small bowel bleeding with very high sensitivity and negative predictive value.